Determinants of repurchase intention in online shopping at shopee - Permata, Kian Getti Prakoso; Nisa, Puspita Chairun (Insight Management Journal, 2024)
The convenience of online shopping in e-commerce applications must be felt by every consumer who uses the application to shop online. This phenomenon is one of the cornerstones in the research conducted by the author. The purpose of this study is to explore the effect of convenience, perceived value, and brand trust on repurchase intentions in the Shopee e-commerce application. The population of this study is made up of people who live in Jakarta, Bogor, Depok, Tanggerang, and Bekasi and use the Shopee application for online shopping. The sample in this study was 125 people. The sampling technique used was the purposive sampling method. The data analysis method used is path analysis through the Partial Least Squares Structural Equation Model (PLS-SEM). Based on the results of the data testing in this study, it can be concluded that convenience has a positive effect on repurchase intentions, convenience has a positive effect on perceived value, perceived value has a positive effect on repurchase intentions, and customer satisfaction has a positive effect on repurchase intentions. This research can be used by E-commerce companies such as Shopee to focus on developing a shopping experience by creating conveniences such as convenience in accessing applications, convenience in transactions, and convenience in maintaining consumer personal information.